World Intellectual Property Indicators, 2021 - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2021)
This authoritative report analyzes IP activity around the globe. Drawing on 2020 filing, registration and renewals statistics from national and regional IP offices and WIPO, it covers patents, utility models, trademarks, industrial designs, microorganisms, plant variety protection and geographical indications. The report also draws on survey data and industry sources to give a picture of activity in the publishing industry. Este informe autorizado analiza la actividad de propiedad intelectual en todo el mundo. Basándose en las estadísticas de presentación, registro y renovación de 2020 de las oficinas de PI nacionales y regionales y la OMPI, cubre patentes, modelos de utilidad, marcas registradas, diseños industriales, microorganismos, protección de obtenciones vegetales e indicaciones geográficas. El informe también se basa en datos de encuestas y fuentes de la industria para dar una imagen de la actividad en la industria editorial.
Keywords: PROPIEDAD INTELECTUAL -- MARCA INTERNACIONAL -- PATENTES